1994
DOI: 10.1016/0014-5793(94)01032-3
|View full text |Cite
|
Sign up to set email alerts
|

Human urokinase receptor expression is inhibited by amiloride and induced by tumor necrosis factor and phorbol ester in colon cancer cells

Abstract: The modulation of urokinase plasminogen activator receptor (uPAR) gene expression by tumor necrosis factor alpha (TNF~), phorbol ester (PMA) and amiloride was studied in three colon cancer cell lines, uPAR mRNA and protein were induced by TNF~ and by PMA but were inhibited by amiloride at concentrations of 0.1 to 1 mM in the presence or absence of TNFc~ and PMA. Nuclear run-on transcription assay indicated that the effects of amiloride and TNF~ were mediated at least in part at the transcriptional level, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 33 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…We and others showed that TGF-b and TNF-a increase expression of uPAR through transcriptional and posttranscriptional mechanisms (15,26,16,33). Because these cytokines have also been reported to regulate LRP-1 expression in other cell types (28,29,34), we sought to determine the role of TNF-a, TGF-b, and IL-1b on LRP-1 expression in PMCs.…”
Section: Discussionmentioning
confidence: 99%
“…We and others showed that TGF-b and TNF-a increase expression of uPAR through transcriptional and posttranscriptional mechanisms (15,26,16,33). Because these cytokines have also been reported to regulate LRP-1 expression in other cell types (28,29,34), we sought to determine the role of TNF-a, TGF-b, and IL-1b on LRP-1 expression in PMCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that expression of uPA and uPAR, as well as their specific interaction, is enhanced by proinflammatory agents, such as LPS, TGF-b, and TNF-a in various cell lines (12,(32)(33)(34)(38)(39)(40)(41). These agents intensely and rapidly induce cell surface uPAR expression and the effect that can be traced back to a rapid, antecedent increase in the cellular level of uPAR mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The uPAR focuses uPA-dependent pericellular proteolysis. In addition, interaction of uPA and uPAR facilitates cellular proteolysis, cell proliferation, adhesion, and migration in diverse cell types of many organs, including lung, during infection or injury (12,32,(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), the toxic moiety of the gram-negative bacterial cell membrane, can enhance uPAR expression on monocytes (5). Although tumor necrosis factor alpha (TNF) is capable of increasing uPAR mRNA levels in monocytic cells and colon cancer cell lines (21,35), reports on the ability of this proinflammatory cytokine to induce uPAR expression on the surface of monocytic cells are conflicting (31,35). After LPS administration to mice, increased uPAR mRNA levels were detected in most tissues examined (4).…”
mentioning
confidence: 99%